Bothrops asper envenoming in cattle: Clinical features and management using equine-derived whole IgG antivenom. (January 2016) - Rodríguez, C.; Estrada, R.; Herrera, M.; Gómez, A.; Segura, Á.; Vargas, M.; Villalta, M.; León, G.
Highlights: Snakebite envenomation is an important problem for the livestock industry in Costa Rica. The clinical manifestations of envenoming by Bothrops asper (family Viperidae) in cattle are described. Accidental envenomation following a B. asper snakebite was reproduced experimentally. The administration of equine-derived whole IgG antivenom was effective in treating B. asper snakebite envenomation. Abstract: Snakebite envenoming is an important problem in the livestock industry in Costa Rica. Of the 22 species of venomous snakes in the country, Bothrops asper is involved in most animal envenomings. Envenomation is typically characterised by swelling and bleeding at the bite site, coagulopathy, systemic haemorrhage, and, in some cases, death. The aims of the present study were to describe the clinical manifestations of B. asper envenomation in cattle and to evaluate the treatment efficacy of antivenom administration. The clinical effects of naturally occurring envenomation were reproduced experimentally in cattle by giving an intramuscular injection of either 10 mg or 50 mg venom to replicate mild and severe envenomings, respectively. Intravenous antivenom given 6 h after experimental venom injection controlled the symptoms; a dose of 120 mL was found to be appropriate for moderate and 200 mL for severe naturally occurring envenomings. Although administration of antivenom within the first 6 h following a snakebite prevented systemic effects, it did not reduce the extent of swelling at the bite site. Delayed administration of antivenom was not effective in saving naturally envenomed animals. The results indicate that, when promptly administered, antivenom constitutes an effective treatment for B. asper snakebite envenomation in cattle.